(untitled) (Scientific journal of the Fergana State University, 2023)
This article touches upon the comparative analysis of the multilevel verbalizers of the microconcept of "subjective–modal assessment”, and for the first time in English, Uzbek and Russian their linguocognitive field nature has been investigated, and the isomorphic and allomorphic features of the constituents of the field have been revealed.